Activity-Based Costing and Profitability A Hybrid Systematic Literature Review and Bibliometric Analysis - Kharimah Murni; Yuliusman Yuliusman; Wirmi Eka Putra; Fredy Olimsar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study employs a systematic literature review integrated with bibliometric analysis to examine the intellectual structure, conceptual evolution, and emerging research trends in the intersection of Activity-Based Costing, profitability, and firm value. Adhering to the PRISMA framework, peer-reviewed articles indexed in the Scopus database, published up to May 2026 and written in English, were systematically identified, screened, and synthesized. Bibliometric techniques facilitated through VOSviewer software were applied to map citation networks, co-authorship patterns, and keyword co-occurrence structures, thereby enabling a thorough examination of the field's thematic development over time. The review demonstrates that academic interest in the relationship between Activity-Based Costing mechanisms, profitability indicators, and firm value has expanded considerably in recent years. Nevertheless, the existing body of literature remains fragmented across diverse methodological approaches and tends to concentrate on specific costing constructs, particularly time-driven frameworks and overhead allocation methods. Prominent contributors, dominant thematic clusters, and notable research gaps are identified, highlighting the necessity for greater theoretical integration, more rigorous causal research designs, and expanded cross-industry comparative analyses. The combination of systematic review and bibliometric mapping establishes a robust analytical foundation, illuminating the trajectory of this research domain and providing clear direction for future empirical and conceptual contributions to cost management and organizational value-creation scholarship.